Prospecção de plantas pioneiras para fitorremediação de solos contaminados por mercúrio - Soares, Camila dos Santos (2024)
Mercury (Hg) is a toxic metal, harmful to health and the environment, which can contaminate the air, soil and water, with consequences for living beings. The prospection of pioneer plantswith characteristics that may be useful in phytoremediation processes of soils contaminated by Hg was carried out. For sampling, 40 sampling points (e.g. empty lots, vacant lots) were demarcated, distributed along the entire urban perimeter of the Municipality of Sinop, Mato Grosso, Brazil. A total of 41 pioneer plant species were identified, distributed in 12 botanical families and, of these, the 16 that had an occurrence greater than or equal to 7.5% of the collection sites were again collected in quintuplicate, as well as the soil around the roots. The Hg concentration was determined in the soil, roots and aerial parts and, from them, the translocation (TF), bioconcentration (BCF) and bioaccumulation (BAF) factors were calculated. The mean Hg concentration in the soil was homogeneous, with an average of 94.7±23.0 μg kg⁻¹, with no significant difference between the different collection points, in the roots it was 50.19±31.9 μg kg⁻¹, with two statistically different groups, and in the shoots, from 32.5 ± 20.5 μg kg⁻¹, also divided into two groups. The species Conyza bonariensis, Emilia sonchifolia, Praxelis clematidea, Euphorbia hirta and Mimosa pudica showed TF between 1.2 and 1.84, statistically equal, and the species Borreria capitata presented the highest TF (3.04), indicating that they are promising for the remediation of soils contaminated by Hg. The BAF showed only the species Mimosa pudica with a value higher than 1 (1.09), showing the ability of this plant to accumulate the metal in the aerial parts, and the species Panicum dichotomiflorum was the only one to present BCF higher than 1.0 (1.11), indicating its ability to accumulate Hg in the roots. Therefore, seven species were selected as promising for phytoremediation because they present at least one of the factors with a value greater than one. Specific studies with laboratory and field simulations must be carried out for the effective application of the technology with a view to the sustainability of production processes and environmental conservation.